Siyasah Syar'iyyah and Local Fiqh Construction: A Study of Islamic Legal Practice in Indonesia - Danil Sutiawan; Roby Saputra; Ifansyah Putra (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
This study aims to describe and analyze the process of adapting Islamic law, particularly fiqh, to local customs and cultures in Indonesia, as well as to identify the factors that influence its success or hindrance. The research method used is qualitative, employing a literature review and case study approach in several regions such as Aceh, Minangkabau, and Java. Data were collected through literature studies, document analysis, and interviews with Islamic scholars and traditional leaders. The results show that the adaptation of Islamic law in Indonesia occurs through the mechanism of ijtihad, emphasizing the principles of maslahah (public interest) and urf (custom) as its main foundation. The integration of fiqh and local customs enhances public acceptance of Islamic law, maintains social harmony, and establishes Islamic law as a contextual living law. However, differences of opinion among scholars and the challenges of modernization remain obstacles that must be wisely managed.